Safety of the Fiocruz ChAdOx COVID-19 vaccine used in a mass vaccination campaign in Botucatu, Brazil - Clemens, Sue Ann Costa; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Crowe, Madeleine; Pollard, Andrew; Tasca, Karen Ingrid [UNESP]; Grotto, Rejane Maria Tommasini [UNESP]; Martins, Marcelo Roberto [UNESP]; Spadaro, André Gasparini; Barretti, Pasqual [UNESP]; Verstraeten, Tom; Clemens, Ralf (Elsevier, 2022)
Introduction: Brazil has been at the core of the COVID-19 pandemic, with the second-highest death toll worldwide. A mass vaccination campaign was initiated on May 16th, 2021, in Botucatu, Brazil, where two doses of ChadOx1-nCoV19 were offered 12 weeks apart to all 18–60- year-olds. This context offers a unique opportunity to study the vaccine safety during a mass campaign. Methods: The first and second doses of the vaccine were administered in May and August 2021, respectively. Emergency room (ER) and hospitalization records were obtained from the Hospital das Clínicas da Faculdade de Medicina de Botucatu for six weeks before and six weeks after the first and second doses, from 4 April to 19 September 2021. Diagnoses with COVID-19-related ICD codes were excluded to distinguish any trends resulting from the COVID-19 pandemic. ER and hospital visits during the two time periods were compared, including an ICD code comparison, to identify any changes in disease distributions. Data were scanned for a defined list of Adverse Events of Special Interest (AESIs), as presented by the Safety Platform for Emergency Vaccines. Results and discussion: A total of 77,683 and 74,051 subjects received dose 1 and dose 2 of ChadOx1-nCoV19, respectively. Vaccination was well tolerated and not associated with any major safety concerns. Increases in ER visits 1 week following both doses were primarily seen in ICD codes related to non-serious side effects of the vaccine, including vaccination site pain and other local events. The neurological AESIs identified (2 of 3 cases of multiple sclerosis) were relapses of a pre-existing condition. One potentially serious hospitalization event for Bell's palsy had onset before vaccination with dose 1, in a patient who also had a viral infection of the central nervous system. There was no myocarditis, pericarditis cases, or vaccine-related increases in thromboembolic events.
Keywords: Adverse events; ChadOx1-nCoV19; COVID-19; Immunisation; Vaccine safety